GHEF 2016: IS OUR HIGHER EDUCATION RESILIENT AND SUSTAINABLE ENOUGH TO FACE THE CHALLENGES AHEAD - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 5 April 2016 – The role of higher education in developing societal resilience and sustainability will be the main focus of the Global Higher Education Forum (GHEF) 2016 which began here today.